Determinación de la resistencia y sensibilidad de cándida al fluconazol en muestras de secreción faríngea en pacientes con vih/sida en el hospital “Carlos Andrade Marín” durante el período de enero a junio del 2015. - Tapia Cárdenas, Myrian Jaqueline (2015)
This research is based on the determination of the resistance and sensitivity of Candida to fluconazole by test antifungigrama, based on the method of disc diffusion proposed by the CLSI, which allows measuring the halo of inhibition of yeast sensitivity to discs, in order to avoid inappropriate treatment. It was performed in pharyngeal secretion samples were taken for patients with HIV / AIDS Carlos Andrade Marín Hospital. The development of the thesis is divided into four sections. Chapter I contains the statement of the problem, the problem formulation, objectives and rationale that led us to conduct this research. Chapter II covers the theoretical framework as the mythological characteristics of Candida clinical forms of oropharyngeal candidiasis, its predisposing factors as well as diagnostic laboratory also has the chemical structure, clinical uses and adverse effects of fluconazole and voriconazole. Chapter III consists of the study methods and instruments and discloses the people with whom we have worked, analysis and interpretation of research results, which were 109 patients with HIV / AIDS showing 100% sensitivity to fluconazole and voriconazole in vitro. Chapter IV covers the recommendations and conclusions.